2002
DOI: 10.1080/00926230252851186
|View full text |Cite
|
Sign up to set email alerts
|

Genital and Subjective Sexual Arousal in Postmenopausal Women: Influence of Laboratory-induced Hyperventilation

Abstract: The current study was aimed at comparing genital and subjective sexual arousal in pre- and postmenopausal women and exploring the effects of heightened sympathetic nervous system (SNS) activity on these parameters. Seventy-one women (25 young and premenopausal, 25 postmenopausal, and 21 age-matched premenopausal women) participated in two counterbalanced sessions consisting of genital arousal assessment with vaginal photoplethysmography and subjective arousal assessment with self-report questionnaires. SNS act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 31 publications
1
29
1
1
Order By: Relevance
“…The relationship between women's physiological and subjective sexual arousal has been controversial (Brotto & Gorzalka, 2002;Laan & Janssen, 2007;Rellini et al, 2005). Our study on younger participants, however, demonstrated a significant relationship for both men and women, though not during the first 5 min of testing for women (Kukkonen et al, 2007).…”
Section: Discussioncontrasting
confidence: 56%
“…The relationship between women's physiological and subjective sexual arousal has been controversial (Brotto & Gorzalka, 2002;Laan & Janssen, 2007;Rellini et al, 2005). Our study on younger participants, however, demonstrated a significant relationship for both men and women, though not during the first 5 min of testing for women (Kukkonen et al, 2007).…”
Section: Discussioncontrasting
confidence: 56%
“…For example, plasma norepinephrine has been shown to correlate with increases in sexual arousal, reaching a peak during orgasm (Exton et al, 1999). Using vaginal photoplethysmography, there were facilitatory effects on sexual arousal of both pharmacological agents (Meston & Heiman, 1998;Rosen, Phillips, Gendrano, & Ferguson, 1999;Rubio-Aurioles et al, 2002) and non-pharmacological interventions (Brotto & Gorzalka, 2002;Meston & Gorzalka, 1995, 1996a, 1996bPalace & Gorzalka, 1990), which increase SNS activity. Meston, Gorzalka, and Wright (1997) found that clonidine, a selective a 2 -adrenergic agonist which inhibits SNS activity, inhibited genital arousal.…”
Section: Sympathetic Nervous System and Female Sexual Arousal Disordermentioning
confidence: 97%
“…Croix, Satoh, Morgan, Skatrud, & Dempsey, 1999) and produces SNS predominance for at least 7 min (Achenbach-Ng, Siao, Mavroudakis, Chiappa, & Kiers, 1994), was used to enhance SNS activity in the current study. LIH has previously been found to significantly facilitate genital sexual arousal in sexually healthy premenopausal women (Brotto & Gorzalka, 2002).…”
Section: Objectives Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…26 Another important finding is that the robust correlation seen in men between subjective arousal and genital congestion (erection) is not seen in women. [27][28][29][30] Rather, sexual arousal in women is more strongly modulated by thoughts and emotions triggered by the state of sexual excitement. 31 In women, photoplethysmography can be used to measure vaginal vasocongestion and hence to gauge physiological arousal.…”
Section: Rosemary Bassonmentioning
confidence: 99%